Curious George and the bunny - Rey, H. A. (Hans Augusto), 1898-1977.; Rey, H. A. (Hans Augusto), 1898-1977 (Boston, Mass. : Houghton Mifflin Co., 1998)
When George the monkey finds a hutch full of bunnies and wonders what it would feel like to hold one, he creates a serious problem for himself.
Cover title.
On board pages.
Keywords: Curious George -- (Fictitious character) -- Fiction; Monkeys -- Fiction; Rabbits -- Fiction